Lithium‐Ion Batteries: 3D Current Collectors for Lithium‐Ion Batteries: A Topical Review (Small Methods 8/2018). Issue 8 (13th August 2018) - Yue, Yuan; Liang, Hong
Abstract : Current collectors play important roles in enhancing the electrochemical performance of lithium‐ion batteries. In article number1800056, Hong Liang and Yuan Yue discuss factors and criteria to better understand the principles of the performance of and thus optimize the design of current collectors. In particular, factors related to the morphological characteristics are discovered. This study leads to new approaches in the design of advanced electrochemical energy‐storage devices.